ROGUE WAVES future-proof your business to survive and profit from radical change. - BRILL, JONATHAN (MCGRAW-HILL EDUCATION, 2021)
"An actionable framework for driving change."-Adam Grant Will the next rogue wave sink your ship-or will you choose to profit from it? At this moment, rogue waves are forming under your business. Emerging technologies, changing demographics, the data economy, automation, and other trends-the undercurrents of radical, systemic change-are crashing into each other. When they converge, they'll produce sea changes that sink companies and wash away entire industries overnight. If your competitor can't ride out the next wave and you can, you win. In Rogue Waves , Jonathan Brill-a renowned expert on resilient growth and decision making under uncertainty-shows you how to prepare your business to survive and thrive through the most radical upheavals. Drawing on years of experience as a Fortune 500 innovation executive, advisor, and entrepreneur, Brill delivers a practical action plan to: Identify and capitalize on the 10 economic, technological, and social trends that will collide to reshape your business Turn sudden threats into outsized opportunities Create a culture of entrepreneurship and experimentation Build and scale leadership skills and processes to supercharge your company's agility and adaptability This must-read survival guide provides the predictive tools you need to take advantage of randomness, turn chaos into profit, and set your company on the course for long-term success.Resilience is your new strategy for growth.